Gamification in English Language Teaching: ICT-Driven Engagement Strategies for 21st Century Learners - Zaenul Wafa; Etika Dewi Kusumaningtyas (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The use of technology in English Language Teaching (ELT) has become an integral part of contemporary educational practices, particularly in supporting student engagement and improving learning outcomes. Among various technology-based approaches, gamification has attracted considerable attention due to its potential to integrate game elements such as points, badges, challenges, and feedback into instructional activities. This study adopts a qualitative library research approach, employing tehmatic content analysisi to review 27 peer-reviewed journal articles published between 2020 and 2025. The selected literature was analyzed to examine how gamification functions as an ICT-based engagement strategy for 21st-century learners in ELT contexts. The review focuses on the role of gamified learning in enhancing learner motivation, engagement, and the development of English language skills, including speaking, listening, reading, and writing. The findings suggest that gamification contributes positively to learner motivation and participation when it is pedagogically designed and aligned with learning objectives. Digital platforms such as Kahoot, Quizizz, and Duolingo are frequently reported as effective tools for facilitating gamified learning. The study concludes that the integration of gamification into ELT curricula can support more meaningful and engaging learning experiences that respond to the characteristics of contemporary learners